2024
DOI: 10.1200/jco.23.01891
|View full text |Cite|
|
Sign up to set email alerts
|

Phase III, Randomized Study of Atezolizumab Plus Bevacizumab and Chemotherapy in Patients With EGFR- or ALK-Rearranged or Translocated Non–Small-Cell Lung Cancer (ATTLAS, KCSG-LU19-04)

Sehhoon Park,
Tae Min Kim,
Ji-Youn Han
et al.

Abstract: PURPOSE In the treatment of non-small cell lung cancer (NSCLC) with a driver mutation, the role of anti-PD-(L)1 antibody following tyrosine kinase inhibitor (TKI) remains unclear. This randomized, open-label, multicenter, phase 3 study evaluates the efficacy of atezolizumab plus bevacizumab, paclitaxel and carboplatin (ABCP) in EGFR or ALK-mutated NSCLC that progressed prior to TKI therapy. METHODS We compared the clinical efficacy of ABCP followed by maintenance therapy with atezolizumab plus bevacizumab with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…On the other hand, the generalisability of our results was supported by the fact that the patients were treated by the same team, which provided an unusual homogeneity of patient selection and care; moreover, the real-life nature of the study ensured patients did not need to go through a screening period that would have excluded rapidly growing tumours. Furthermore, a reallife study was the only option available to assess patients with untreated brain metastases in Europe, and the only way to contextualise the degree of patient selection of prospective studies that tested ABCP [23,24,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the generalisability of our results was supported by the fact that the patients were treated by the same team, which provided an unusual homogeneity of patient selection and care; moreover, the real-life nature of the study ensured patients did not need to go through a screening period that would have excluded rapidly growing tumours. Furthermore, a reallife study was the only option available to assess patients with untreated brain metastases in Europe, and the only way to contextualise the degree of patient selection of prospective studies that tested ABCP [23,24,36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent chemo-immunotherapy studies have shown heterogeneous results in patients with actionable mutations [24,[33][34][35][36]. On the one hand, randomised studies with Pemetrexed-containing combinations [33][34][35] showed disappointing results; on the other hand, studies using Paclitaxel and Bevacizumab [24,36] consistently showed therapeutic efficacy, especially in patients with brain metastases, PDL1 ≥ 1%, and/or ALK translocated lung cancers. This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ORI-ENT-31 study confirmed that ICI combined with anti-angiogenic therapy and chemotherapy significantly improved PFS in EGFR-mutant non-squamous NSCLC patients who progressed after treatment with EGFR-TKIs [31]. Although the IMpower150 [32], ORIENT-31 and ATTLAS/KCSG-LU19-04 [33] studies have unanimously confirmed that patients with EGFR-TKI-resistant NSCLC can benefit from the four-drug combination therapy of immune + platinumcontaining double-drug chemotherapy + bevacizumab. However, the four-drug combination regimen has a higher incidence of adverse effects and is limited in clinical use.…”
Section: Egfr Mutationsmentioning
confidence: 97%
“…10 Similarly, the ATTLAS study further confirmed the efficacy of atezolizumab plus bevacizumab, carboplatin, and paclitaxel in patients whose illness progressed while receiving TKI treatment. 11 The ORIENT-31 trial showed that sintilimab plus bevacizumab biosimilar IBI305, pemetrexed, and cisplatin resulted in significant improvement in PFS compared with chemotherapy alone for patients whose illness progressed while receiving EGFR-TKI therapy. 12 Although, the IMpower151 study did not meet the primary end point, which also used the 4 drug combination regimen (atezolizumab plus bevacizumab, carboplatin, and pemetrexed or paclitaxel), the subgroup analysis showed that patients who experienced resistance to first-or second-generation EGFR-TKI treatment could benefit more, with a hazard ratio (HR) of 0.55 (95% CI, 0.29-1.02).…”
mentioning
confidence: 99%